The Impact of the 2025 Flood Disaster in Bali on the Image of Tourism Destinations - Febriani Rahmawati Gulo; Epelina Oktavia (Takaza Innovatix Labs Ltd., 2026)
Bali is a leading Indonesian tourist destination that relies heavily on a positive image to attract tourists. The flood disaster that occurred in late 2024 to early 2025 had various impacts on the tourism sector, both physically and psychologically. This study aims to analyze the impact of the 2025 flood disaster on the image of tourist destinations in Bali. The study used a descriptive qualitative approach with a phenomenological method. Data were obtained through in-depth interviews with tourists and local residents selected using purposive sampling techniques, supported by literature and documentation studies. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the floods impacted Bali's destination image, particularly in aspects of safety, comfort, and accessibility. Mass media and social media coverage were the main factors shaping tourists' risk perceptions. However, this impact was temporary because Bali's positive image, supported by its rich culture, natural beauty, friendly people, and international reputation, continued to maintain tourist interest. Furthermore, recovery efforts undertaken by the government and tourism industry players through infrastructure improvements, destination promotion, and improved service quality also played a role in restoring tourist confidence. This study shows that although natural disasters can affect a destination's image in the short term, the strength of the destination's identity and uniqueness plays an important role in maintaining a positive image in a sustainable manner.